KONSELING INDIGENOUS BERBASIS PESANTREN: Teknik Pengubahan Tingkah Laku Kalangan Pesantren - Samsul Arifin (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2013)
Sanctions in Islamic Boarding Schools (Pesantren) are known as ta'zir. Ta'zir belongs to one of behavioral alteration techniques in boarding school style. Counseling unearthed from the values of boarding school need to be studied to develop counseling model based on the culture of Indonesia. This research is important-especially for counselors in educational institutions based on Islamic boarding schools so that they know the traditions related to guidance and counseling. This study is focused on the values of the pesantren which can be absorbed in guidance and counseling. It is a technique in changing counselee behavior. The results of this study are; ta'zirÂ  which is applied in Islamic boarding school aims to turn students into good behavior. Among Ta'zir principles in boarding schools are educational (ta'dib), noticing the social situation and the condition of the perpetrator (i'tibar ahwal an-nas), and being carried out gradually (at-tadrij). The three characteristics of ta'zir imply that the ta'zir is done without violence. Such a ta'zir is similar to the concept of punishment (in the behavioral counseling).